2002
DOI: 10.1016/s0094-1190(02)00017-7
|View full text |Cite
|
Sign up to set email alerts
|

Car ownership, employment, and earnings

Abstract: for many helpful comments. We are especially grateful to Michael Provence for first suggesting the empirical strategy pursued here. This research was supported by a grant from the National Science Foundation, SBR-9709197 and a grant from the Joint Center for Poverty Research. AbstractIn this paper, we attempt to assess whether the positive effects of car ownership on employment outcomes observed in past research are causal. We match state-level data on average car insurance premiums and average per-gallon gas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
143
2
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(158 citation statements)
references
References 17 publications
8
143
2
5
Order By: Relevance
“…However, the results showed that the relevant variable was not the time cost to access jobs but rather the car availability in the household. This result agrees with other studies Rice, 2002 andOng andMiller, 2005) and reflects that private transport is sometimes the only option to connect residential places and job opportunities. …”
Section: The Datasupporting
confidence: 93%
“…However, the results showed that the relevant variable was not the time cost to access jobs but rather the car availability in the household. This result agrees with other studies Rice, 2002 andOng andMiller, 2005) and reflects that private transport is sometimes the only option to connect residential places and job opportunities. …”
Section: The Datasupporting
confidence: 93%
“…Holzer et al (2003) find that the expansion of the railway system in San Francisco to a predominantly White, high-growth and lowunemployment suburb increases the relative employment of minority workers near the station. Raphael and Rice (2002) show that car ownership increases the employment rate and the number of hours worked but, surprisingly, decreases hourly earnings. Ong and Miller (2005) show that the 'transportation mismatch' (the lack of access to a private automobile) is the most important factor in generating poor labour market outcomes, particularly for disadvantaged neighbourhoods in the Los Angeles metropolitan area.…”
Section: Spatial Mismatch: the Workers' Perspectivementioning
confidence: 93%
“…Income is found to be a determinant for car ownership and use both for work and non-work purposes, which also may be one of the most important factors [49,50]. Yet some researchers claim that the relationship between income and VMT is not significant [38].…”
Section: Other Factors Influencing Car Ownership and Usementioning
confidence: 99%